Optimasi Konfigurasi Mainjet Dan Slowjet Karburator Motor Bensin Satu Silinder 97 Cc - Prawoto Prawoto (Universitas Muhammadiyah Yogyakarta, 2006)
This paper describes a study that compared performance and emission from a 97 cc small single cylinder gasoline engine using five differences carburetor jet configuration. The study is based on the engine test bed results. The test results have shown that the bigger main jet produce slightly higher torque and power than the smaller one, but the fuel consumption also higher. The emission test results have shown a higher hydrocarbon (HC) and carbon monoxide (CO) for bigger main jet configuration. However Oxide of Nitrogen (NOx) emission from bigger main jet configuration was generally lower. The smallest jet configuration produced to lean fuel air mixture and caused engine over heat. The data obtained in this study indicate that the best configuration for the engine tested is 72/38 jet configuration.